1980
DOI: 10.1159/000468441
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Multicentre Trial Comparing the Efficacy and Side-Effects of Mianserin and Chlorimipramine in Depressed In- and Outpatients

Abstract: Mianserin (60 mg daily) was compared with chlorimipramine (150 mg daily) in the treatment of 145 depressed in- and outpatients in four centres. The trial was double-blind and fully randomized. Both drugs were effective antidepressants. No significant differences in efficacy could be demonstrated by means of the Hamilton rating scale for depression, the Beck self-rating scale or the clinical global impression, for both in- and outpatients. Hypotension, dry mouth and tremor increased significantly more in inpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Taken together and consistent with the findings in humans in regards to obesity [33], [34], we find that antidepressants of the serotonin antagonist-type do not extend C.elegans lifespan at most commonly used and generally accepted experimental conditions.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Taken together and consistent with the findings in humans in regards to obesity [33], [34], we find that antidepressants of the serotonin antagonist-type do not extend C.elegans lifespan at most commonly used and generally accepted experimental conditions.…”
Section: Resultssupporting
confidence: 89%
“…Accordingly, and to test whether solid phase media as used in our C.elegans experiments reflect the situation in humans, we have tried to replicate the fact that mianserin increases human body mass [34] by applying this compound to nematodes. Indeed, both compounds significantly increased body fat after ten days of incubation at the concentrations that have been used by Petrascheck and colleagues [24] (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the antidepressive effects, mianserin also has some anxiolytic features 5 . Various double‐blind studies have demonstrated that mianserin is as effective an antidepressant as imipramine, 6 amitriptyline, 7 or clomipramine, 8 at the same time having a less incidence of anticholinergic side effects 7,9 …”
mentioning
confidence: 99%